2011
DOI: 10.18632/oncotarget.333
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia stem cells in the era of targeted therapies: resistance, persistence and long-term dormancy

Abstract: Targeted therapies of chronic myeloid leukemia (CML) using tyrosine kinase inhibitors (TKI) have profoundly changed the natural history of the disease with a major impact on survival. Molecular monitoring with BCR-ABL quantification shows that a status of undetectable molecular residual disease (UMRD) is obtained in a significant minority of patients. However, it remains unclear whether these patients are definitively cured of their leukemia. Imatinib mesylate withdrawal trials have demonstrated the rapid appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 114 publications
(121 reference statements)
0
49
0
Order By: Relevance
“…Despite advances in melanoma research and drug development, 10-20% of clinically disease-free patients relapse 5-10 years following an initial treatment [1,2]. This phenomenon, which is known as tumor dormancy [3], has been related to the existence of therapy-resistant cells with stem-like activity [4][5][6]. Recent findings suggest that cancer stem cells, in response to chemotherapy, enter protective, prolonged, but reversible, quiescence [7] and remain dormant without causing any clinical manifestations until activated [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in melanoma research and drug development, 10-20% of clinically disease-free patients relapse 5-10 years following an initial treatment [1,2]. This phenomenon, which is known as tumor dormancy [3], has been related to the existence of therapy-resistant cells with stem-like activity [4][5][6]. Recent findings suggest that cancer stem cells, in response to chemotherapy, enter protective, prolonged, but reversible, quiescence [7] and remain dormant without causing any clinical manifestations until activated [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is still unclear how typical MDR (ABC transporters) and atypical MDR (non ABC transporters) are regulated and how they fit into the new molecular target therapy. [46][47][48] Our previous work demonstrated that LRPPRC was potentially involved in IM and MDR cross-resistance. LRPPRC is a 130 kDa protein that was first described in hepatocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The controls u, u 1 and u 2 stand for the drug effects on CML cells. Since the exact effect of Imatinib on the leukemic cells is still under debate (see the review by Chomel et al 2011 [10]), it is important to explore all possibilities. However, it is known that, because Imatinib is a tyrosine kinase inhibitor, it does not directly kill the leukemic cells, but slows down their proliferation and stabilizes all other abnormal processes that provide cancerous cells a proliferative advantage.…”
Section: The Modelmentioning
confidence: 99%